2020
DOI: 10.3390/nu12010248
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulated Tuna Oil Results in Higher Absorption of DHA in Toddlers

Abstract: Docosahexaenoic acid (DHA) is an essential component for brain and visual acuity development during foetal and early postnatal life. A newly released directive under the European Commission stipulates DHA as a mandatory ingredient in infant formula. This poses challenges to manufacturers in preserving the stability and bioavailability of DHA at levels akin to human breast milk. The aims of this study were (a) to investigate the bioavailability of microencapsulated omega-3 DHA formulations in healthy toddlers c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…In the present study, the dose of 1.6g of combined EPA and DHA for 12 weeks was effective in increasing the HS-Omega-3 Index ® by almost 3-fold (i.e., 9.7%), suggesting that HiDHA powders are highly bioavailable. This may be due to the microencapsulation of the tuna oil, which reduces oxidation and the small surface area of the particles which are more easily accessible by enzymes allowing greater solubility and absorption [44]. A recent systematic literature review has suggested that the microencapsulated form of omega-3 are more bioavailable compared to standard fish oil [45].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the dose of 1.6g of combined EPA and DHA for 12 weeks was effective in increasing the HS-Omega-3 Index ® by almost 3-fold (i.e., 9.7%), suggesting that HiDHA powders are highly bioavailable. This may be due to the microencapsulation of the tuna oil, which reduces oxidation and the small surface area of the particles which are more easily accessible by enzymes allowing greater solubility and absorption [44]. A recent systematic literature review has suggested that the microencapsulated form of omega-3 are more bioavailable compared to standard fish oil [45].…”
Section: Discussionmentioning
confidence: 99%
“…Minimal adverse events were reported. Driphorm ® HiDHA ® powders have been used previously in younger children at a lower dose and were also tolerated well [45].…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated improved bioavailability with considerably higher blood DHA levels in formulations using microencapsulated powders DHA content of toddler feces decreased from 4.1 to 3.1-2.7 ng/g, indicating the improved absorption and reduced fecal loss in toddler's body Fard et al (2020) Abbreviations: ALA, α-linolenic acid; ARA, arachidonic acid; DHA, docosahexaenoic acid; EPA, eicosapentaenoic acid; FA, fatty acid; LA, linoleic acid; PUFA, polyunsaturated fatty acids; SFA, saturated fatty acids.…”
Section: Emulsificationmentioning
confidence: 91%
“…FAs detected in blood and feces were used to evaluate the bioavailability of DHA and other FA. Even though the treatment did not significantly affect sleep and crying patterns, the results showed that formulas containing microencapsulated powders had improved bioavailability and significantly higher blood DHA levels (Fard et al., 2020).…”
Section: Health Benefits Of Encapsulated Omega‐3 Fatty Acid‐rich Oilsmentioning
confidence: 99%